Pemanfaatan Ekstrak Jahe dan Mentimun Menjadi Plaster Luka Bakar dengan Penambahan Alga sebagai Biofilm - Mariza Ainun Jariyah; Susanti Rahayu; Giesty Trienita (Jurnal Integrasi Sains dan Quran, 2025)
The skin, the body's largest organ, plays a key role in protection, temperature regulation, sensation, sweat excretion, and vitamin D synthesis. It also serves as a barrier against external agents and prevents fluid loss. However, the skin is highly susceptible to damage, including burns caused by tissue damage due to heat. The WHO says burns cause about 180,000 deaths a year. But first and second-degree burns can be treated at home.This study developed an algae-based burn bandage with ginger and cucumber extracts in hydrogel to protect the wound from bacteria and facilitate skin regeneration. The study used a qualitative descriptive method to test the effectiveness of ginger and cucumber extracts in a hydrogel for wound treatment and the convenience of using biofilm.The tests included antimicrobial, skin irritation, solubility, biodegradable, elasticity, and organoleptic tests.The study found that the active components in the product can eradicate bacterial microbes, ensuring its safety, and dissolve in water within three days. The product's properties include elasticity, easy decomposition, a noticeable ginger aroma, a soft and chewy texture, and a slightly dark, clear color.